Nancy Clark's sports nutrition guidebook - Clark, Nancy (Canada : Human Kinetcs, 2008)
Nancy Clark's Sports Nutrition Guidebook will help you make the right food choices in grocery stores, restaurants, drive-throughs, and your own kitchen. Whether you're preparing for competition or simply eating on the go, let sport's leading nutritionist show you how to get maximum benefit from the foods you choose and the meals you make. You'll learn how to eat before exercise and events as well as how to refuel afterward for optimal recovery." "Updated and on the cutting edge, the fourth edition includes the latest sports nutrition research on hydration and fluid intake, vitamins, supplements, energy drinks, organic foods, and the role of carbohydrate and protein during exercise. You'll also learn about the new food pyramid and the American Heart Association's latest dietary guidelines.
Part I. Everyday Eating for Active People -- Part II. The Science of Eating for Sports Success -- Part III. Balancing Weight and Activity -- Part IV. Winning Recipes for Peak Performance .
Includes index.
Keywords: ATHLETES NUTRITION